Histology of pediatric classic Hodgkin lymphoma: From diagnosis to prognostic stratification. Issue 5 (5th March 2020) - Pizzi, Marco; Tazzoli, Sara; Carraro, Elisa; Chaviano, Felicia; Massano, Davide; Lovisa, Federica; Mussolin, Lara; Todesco, Alessandra; Biffi, Alessandra; d'Amore, Emanuele S.; Pillon, Marta; Rugge, Massimo
Abstract: Aims: Classic Hodgkin lymphoma (cHL) is a common malignancy of the pediatric age. Although clinical‐radiological features are routinely used for disease risk stratification, the role of tumor histology has yet to be defined. This study aimed to characterize the clinical‐pathological features of a large cohort of pediatric cHL specifically investigating the relevance of tumor histology for the prognostic stratification of patients. Methods and results: The study considered 96 clinically annotated cases of pediatric cHL treated according to the AIEOP‐LH2004 protocol. The following histological parameters were considered: (i) cHL variant; (ii) grade of nodular sclerosis (NS); (iii) staining for Bcl2 and p53, and expression of B‐cell (BCA) and T‐cell antigens (TCA) by Hodgkin/Reed‐Sternberg cells. The study population consisted of 51 males and 45 females (median age: 13.6 years) with five‐year overall and progression‐free survival of 94% and 81%, respectively. Most cases featured NS morphology (96%) with a prevalence of NS1 over NS2 grades. Two NS2 variants were recognized (sarcomatous/syncytial and fibrohistiocytic). A consistent subset of cases disclosed positivity for BCA (34%), TCA (26%), p53 (13%), and Bcl2 (19%). Clinical‐pathological correlations showed a more aggressive clinical course for NS2 over NS1 cases. The NS2 fibrohistiocytic variant was associated with the worst outcome. No other histological features correlated with prognosis. Conclusions: Pediatric cHL is a clinically and histologically heterogeneous neoplasm. The majority of cases disclose NS morphology and aberrant phenotypes are frequently encountered. In the pediatric population, NS grading and NS2 subtyping bear significant prognostic impact.